(untitled) (Al-Academy, 2025)
The Arts in the totality of human achievements are related in productive , social and mental terms, and ancient Greek culture is a set of achievements in the field of material culture of Greek society during the period of its formation, prosperity and decline. The heyday of its classical heritage dates back to the time of Athenian democracy , as ancient civilizations paved the way for world culture, as Greek art can be considered the ancestor of any art that exists today, especially in the history of European civilization, and it had a great influence on the development of the Middle Ages, and therefore the modern world, as the cultural heritage of ancient civilizations: What are the formal elements of architecture and interior design and their reflections in contemporary interior design The aim of the current research is to reveal the formal elements of Cretan-Mycenaean architecture and its references , and what are its structural and formal elements that can be employed in interior design . The current research consists of two researches : the first: the intellectual and historical references of Cretan-Mycenaean architecture: the second research: the Cretan-Mycenaean style in architecture and interior space: and the procedures of his research ,which followed the descriptive approach and reached statistically proven results, and the most important conclusions: 1. It employs decorative facades that correspond to the tradition and geometric patterns that decorated the palace of Knossos, as well as employing short conical columns, which is characteristic of columns in Cretan-Mycenaean architecture.2. The main entrances are designed inspired by the famous Lions Gate in Messina or nature environments, and use natural patterns inspired by flowers, animals, sea creatures or symbols associated with religious rituals